Assessment of green sustainable development in plateau lakeside cities - Peng, Changqing; Yang, Kun; Jia, Tingfang; Shang, Chunxue; Li, Anling; Pei, Xingfang; Wang, Qingqing; Chen, Rixiang; Li, Dingpu; Luo, Yi (Frontiers in Ecology and Evolution, 2024)
IntroductionGreen sustainable development is an important part of the United Nations Sustainable Development Goals (SDGs) and China’s ecological civilization construction.MethodsThis paper combines the characteristics of the development of lakeside cities, gives full play to the advantages of modern remote sensing technology to collect the indicators related to the green sustainable development of lakeside cities, adopts the Analytic Hierarchy Process (AHP) and the CRiteria Importance Through Inter-criteria Correlation (CRITIC) subjective and objective weighting methods and the difference coefficient method to determine the weights of the indicators, evaluates the green sustainable development of a typical lakeside city of Kunming for more than 30 years, and analyzes the influencing factors using the gray degree of correlation.ResultsThe results show the following: (1) From 1990 to 2021, the level of green sustainable development in the urban area around Dianchi Lake fluctuated in stages, with an overall upward trend, and the green development index increased from 0.25 in 1990 to 0.5 in 2021. (2) The coefficient of variance determined by the optimization model can be a better compromise between the objective and subjective weights of the indicators, and the massive occupation of wetlands and arable land around the lake in the urban expansion has become a major factor in the development of the city, with a combined weight of 10.30% and 8.79%, respectively. (3) The urban population and economic scale are currently the main drivers of the green and sustainable development of a lakeside city, with a correlation of 0.843 and 0.769, respectively.DiscussionThe growth of urban population and economic scale plays a pivotal role in driving the green and sustainable development of lakeside cities, while the potential impact of tourism development should also be considered.